2008
DOI: 10.1093/jac/dkn033
|View full text |Cite
|
Sign up to set email alerts
|

Selective pressure affects transfer and establishment of a Lactobacillus plantarum resistance plasmid in the gastrointestinal environment

Abstract: The overall results imply that the gastrointestinal tract may comprise a more favourable environment for antibiotic resistance transfer than conditions provided in vitro. However, the indigenous gut microbiota severely restricts transfer, thus minimizing the number of detectable transfer events. Treatment with erythromycin strongly favoured transfer and establishment of pLFE1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 35 publications
2
82
0
Order By: Relevance
“…In the diassociated model pAMβ1 has been transferred from L. reuteri to Enterococcus faecalis (Morelli et al, 1988). Interspecies conjugative transfer of tetracycline and erythromycin resistance plasmids from lactobacilli has been demonstrated previously in vitro (Gevers et al, 2003a;Ouoba et al, 2008;Feld et al, 2008 Transfer has been demonstrated in the GIT of rodents, both gnotobiotic (Feld et al, 2008;Jacobsen et al, 2007;Morelli et al, 1988) and those having an indigenous gut microbiota (Feld et al, 2008;Jacobsen et al, 2007;Schlundt et al, 1994;McConnell et al, 1991;Gruzza et al, 1994;Igimi et al, 1996). In addition, the in vivo transfer of vancomycin resistance has recently been shown between enterococci and probiotic lactobacilli in gnotobiotic mice (Mater et al, 2008).…”
Section: Evidence Of Potential Horizontal Gene Transfer Of Probiotic mentioning
confidence: 98%
See 3 more Smart Citations
“…In the diassociated model pAMβ1 has been transferred from L. reuteri to Enterococcus faecalis (Morelli et al, 1988). Interspecies conjugative transfer of tetracycline and erythromycin resistance plasmids from lactobacilli has been demonstrated previously in vitro (Gevers et al, 2003a;Ouoba et al, 2008;Feld et al, 2008 Transfer has been demonstrated in the GIT of rodents, both gnotobiotic (Feld et al, 2008;Jacobsen et al, 2007;Morelli et al, 1988) and those having an indigenous gut microbiota (Feld et al, 2008;Jacobsen et al, 2007;Schlundt et al, 1994;McConnell et al, 1991;Gruzza et al, 1994;Igimi et al, 1996). In addition, the in vivo transfer of vancomycin resistance has recently been shown between enterococci and probiotic lactobacilli in gnotobiotic mice (Mater et al, 2008).…”
Section: Evidence Of Potential Horizontal Gene Transfer Of Probiotic mentioning
confidence: 98%
“…Resistance to tetracycline has been observed more often among lactobacilli (Roberts, 2005;Korhonen et al, 2008). Resistance against neomycin, kanamycin, streptomycin and gentamicin (aminoglycosides) has been observed more frequently among lactobacilli (Coppola et al, 2005;Danielsen, 2002;Zhou et al, 2005).…”
Section: Antibiotic Resistance Of Probiotic Lactobacillimentioning
confidence: 99%
See 2 more Smart Citations
“…10 Although the observations of the present study indicate that CFS has the potential to augment the efficacy of antibiotics but the possibility of transfer of resistance genes from L. plantarum (if given as such) to Salmonella cannot be ruled out as has been reported in case of other microorganisms. 23,24 This issue needs to be explored further in reference to Salmonella infections. …”
mentioning
confidence: 99%